DEVELOPMENT OF STUDENTS' ABILITY TO ENGAGE IN GROUP ACTIVITIES IN TECHNOLOGY - Dusyarov Xudoymurod Chorshanbiyevich (Journals Park Publishing, 2024)
In this article, attention is paid to the organization of technology classes and the development of students' creative abilities during the classes.
Keywords: Technology, science, circle activities, extracurricular activities, students' creative abilities, development, methods and methods, form, instruction (guidance), research, aspiration.